Risk Factors for Acanthamoeba Keratitis—A Multistate Case–Control Study, 2008–2011. (September 2018) - Brown, Allison C.; Ross, Jonathan; Jones, Daniel B.; Collier, Sarah A.; Ayers, Tracy L.; Hoekstra, Robert M.; Backensen, Bryon; Roy, Sharon L.; Beach, Michael J.; Yoder, Jonathan S.
Abstract : Objective: To identify modifiable risk factors contributing to Acanthamoeba keratitis (AK) infection. Methods: A case–control investigation was conducted. Case patients were soft contact lens wearers with laboratory-confirmed AK. Control were soft contact lens wearers ≥12 years of age, with no history of AK. Case patients were recruited from 14 ophthalmology referral centers and a clinical laboratory. Control were matched on state of residence and type of primary eye care provider (ophthalmologist or optometrist). Participants were interviewed using a standardized questionnaire. Univariable and multivariable conditional logistic regression analyses were conducted. Matched odds ratios (mORs) were calculated. Results: Participants included 88 case patients and 151 matched control. Case patients were more likely to be aged <25 years (unadjusted mOR 2.7, 95% confidence interval 1.3–5.5) or aged >53 years (mOR 2.5, 1.1–5.7), and more likely to be men (mOR 2.6, 1.4–4.8). Unadjusted analyses identified multiple risk factors: rinsing (mOR 6.3, 1.3–29.9) and storing lenses in tap water (mOR 3.9, 1.2–12.3), topping off solution in the lens case (mOR 4.0, 2.0–8.0), having worn lenses ⩽5 years (mOR 2.4, 1.3–4.4), rinsing the case with tap water before storing lenses (mOR 2.1, 1.1–4.1), and using hydrogen peroxide (mOR 3.6, 1.1–11.7) versus multipurpose solution. Significant risk factors in multivariable modeling included age >53 years, male sex, topping off, and using saline solution. Conclusions: Numerous modifiable risk factors for AK were identified, mostly involving hygiene practices. To reduce the risk of AK, lens wearers should observe recommended lens care practices. Abstract : Supplemental Digital Content is Available in the Text.